COACHING AS THE PEDAGOGICAL TECHNOLOGY IN PROFESSIONAL TRAINING OF FUTURE SPECIALISTS - Dzikovska, Mariia (Continuing Professional Education: Theory and Practice, 2019)
The article deals with theoretical analysis of coaching – as innovative pedagogical technology. Relying on a comparative analysis of scientific and pedagogical sources, the author notes common problems in the scientific research of domestic and foreign scientists. It is pointed out that the technology of coaching went through the theoretical analysis, wide practical application in the theory and practical research by foreign scientists. It is shown that common features in domestic and foreign studies of coaching are: the construction of educational processes based on motivational interaction; creation of opportunities to disclose individual’s potential; the equitable creative activity of participants in the educational process; partnership to support people in achieving their goals. It has been proved that coaching has all signs of pedagogical technology, common pedagogical activity model of design, organization, and introduction in the educational process; the organizational component of the structure of different forms in native classes, other types realization of pedagogical consideration of subjects in educational process; Possibility for the development of the student’s personal potential and realization of teacher’s potential; The stages of coaching realization on the basis of knowledge are characterized (twelve stages with realization of practical tasks on each of them). The author identifies the benefits (enhancement of the activation of the educational process and the motivation of students to study the course, identify students’ abilities that reveal them as creative people capable of logical thinking, the development of students leadership qualities and emotional intelligence, high productivity of the educational process and the improvement of communication skills) and the disadvantages of using coaching technology in the training of future specialists in a higher education institution. It is shown that coaching develops leadership skills for students, which stimulates the formation of successful teams that provide training for competent professionals in a higher education institution.